PEMBINAAN KARAKTER MAHASISWA MELALUI PENGEMBANGAN MATRIKULASI KEPRIBADIAN - _, MAGDALENA (Institut Agama Islam Negeri Padangsidimpuan, 2015)
The emergence of Islamic education institutions was driven by the necessity to build character. One of the Islamic institutions that deal with these necessity above is Islamic higher education. By taking a case in IAIN Padangsidimpuan, one of character building is used in it is Matrikulasi Kepribadian that can be used to build character knowing, feeling, and action to applicate the students’ character on life. But, in dealing with the purpose that the leader management must improve many aspects to get the better result in character building, as educational management in Matrikulasi Kepribadian, method, and funding.